Pengukuran Literasi Digital Mahasiswa Pendidikan Teknik Arsitektur sebagai Digital Native pada Era Revolusi Industri 4.0 - Mufti Muhammad Reyhan, - (2020)
The head of research is "The Digital Literacy Measurement of Architecture Engineering Education Students as Digital Native at The Era of Industrial Revolution 4.0. This study aim at measure the digital literacy of Architectural Engineering Education students in the Faculty of Technology and Vocational Education in the process of transition to a new normal at Industrial Revolution 4.0 era that will disrupt entire sectors into digital format. The method that the researcher used in this study is descriptive research with quantitative approach and the questionnaire with psychological approach is the data accumulation technique that the research used to collect the data. The questionnaire distributed to Architectural Engineering Education students online. And also, for the sampling technique is purposive sampling by taking into account special features. The measurements of digital literacy observed in 3 dimension of Architectural Engineering Education students' digital literacy that is technical dimension, cognitive dimension and social-emotional dimension. The graphic diagram pre dimension informed the research's result.